Amino Acid Residues 68–71 Contribute to Influenza A Virus PB1-F2 Protein Stability and Functions - Cheng, Yi-Ying; Yang, Shih-Rang; Wang, Ying-Ting; Lin, Yu-Hsin; Chen, Chi-Ju (Frontiers in Microbiology, 2017)
Influenza A virus PB1-F2, encoding a multi-functional protein, is regarded as a virulent gene. Variation in expression pattern and protein stability among PB1-F2 proteins derived from different strains may explain why PB1-F2 functions in a strain- and cell type-specific manner. Because the protein stability of PB1-F2 affects its biological functions, we looked for sequences important for this property. By comparing variants and chimeric of PB1-F2 proteins from A/Hong Kong/156/1997 (H5N1) and A/Puerto Rico/8/1934 (H1N1), we identified amino acid residues 68-71 affect its protein stability. PB1-F2 with T68, Q69, D70, and S71 has a shorter protein half-life than its I68, L69, V70, and F71 counterpart. This is likely to do with proteasome-mediated degradation. Swapping amino acids 68-71 between two proteins reversed not only the length of protein half-life and sensitivity to MG132, but also subcellular localization and interferon antagonization. Our data suggested that composition of amino acids 68-71, which regulates protein stability and therefore its functions, can be a major factor determining strain-specificity of PB1-F2.